2023
DOI: 10.7759/cureus.41758
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Spinal Neuroschistosomiasis in Yemen: An Overlooked Dilemma in an Endemic Region

Nabil Aljuma'ai,
Saif A Ghabisha,
Faisal Ahmed
et al.

Abstract: Background: Neurological involvement in schistosomiasis presents a significant and serious complication. While the disease is generally considered treatable during the early stages, the rarity of this condition often leads to delays in diagnosis and treatment. This study aims to report the clinical characteristics of pediatric patients with spinal neuroschistosomiasis (NS) in an endemic area to the disease.Methods: A retrospective cross-sectional review was conducted at Althora General Hospital in Ibb, Yemen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…3 Achieving positive treatment outcomes is heavily reliant on early detection and timely treatment with the administration of high-dose steroids and praziquantel. 4 Despite the relatively favorable prognosis, delayed recognition and intervention can be associated with permanent neurological deficits. 2 While post-mortem studies have indicated a three to four times higher prevalence rate of asymptomatic NS cases, 5 the variability of clinical presentation and low index of suspicion can lead to misdiagnosis, even among symptomatic cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Achieving positive treatment outcomes is heavily reliant on early detection and timely treatment with the administration of high-dose steroids and praziquantel. 4 Despite the relatively favorable prognosis, delayed recognition and intervention can be associated with permanent neurological deficits. 2 While post-mortem studies have indicated a three to four times higher prevalence rate of asymptomatic NS cases, 5 the variability of clinical presentation and low index of suspicion can lead to misdiagnosis, even among symptomatic cases.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the presentation of NS can be nonspecific, mimicking transverse myelitis or intra‐axial spinal tumors, particularly with conus intramedullary extension 3 . Achieving positive treatment outcomes is heavily reliant on early detection and timely treatment with the administration of high‐dose steroids and praziquantel 4 . Despite the relatively favorable prognosis, delayed recognition and intervention can be associated with permanent neurological deficits 2 .…”
Section: Introductionmentioning
confidence: 99%